Immunoexpression of integrins in ameloblastoma, adenomatoid odontogenic tumor, and human tooth germs - Andrade, Emanuel Sávio de Souza (2008)
The expression of integrins alpha2beta1, alpha3beta1, and alpha5beta1 in 30 ameloblastomas (20 solid and 10 unicystic tumors), 12 adenomatoid odontogenic tumors (AOTs), and 5 human tooth germs in different stages of odontogenesis was analyzed. The distribution, location, pattern, and intensity of immunohistochemical expression were evaluated. Intensity was analyzed using scores (0 = absence, 1 = weak staining, and 2 = strong staining). No difference in the immunoexpression of the integrins was observed between solid and unicystic ameloblastomas. When these two ameloblastoma types were pooled into a single group, the following significant differences were found: immunoexpression of integrin alpha2beta1 was stronger in ameloblastomas than in AOTs and tooth germs, and the expression of integrin alpha5beta1 was stronger in ameloblastomas than in AOTs. The lack of detection of integrin alpha3beta1 in tooth germs and its detection in the odontogenic tumors studied suggest that this integrin might be used as a marker of neoplastic transformation in odontogenic tissues.